Clinical and Demographic Profiles of Patients Diagnosed as Cough Variant Asthma attended at Tertiary Referral Hospital - Hossain, SK Shahinur; Islam, Md Safiul; Rahman, Md Mustafizur; Dey, Shubhashish; Mahmud, Khurshid (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Cough variant asthma is presented with different clinical and demographic characteristics. Objectives: The purpose of the present study was to see the clinico-demographic profiles of cough variant asthma patients. Methodology: This descriptive type of cross-sectional study was carried out in the Department of Respiratory Medicine at National Institute of Diseases of the Chest and Hospital (NIDCH), Dhaka, Bangladesh from September 2014 to August 2015 for a period of one year. Patients presented with cough variant asthma attending in NIDCH were selected as study population. Methacholine challenge test was performed to diagnosis of Cough Variant Asthma. Result: A total number of 50 patients were recruited for this study. The mean age±SD was found 19.1±7.6 years. Male was predominant than female with a ratio of 1.4.:1. Among the study population positive family history of asthma was found in 39.0% cases and associated allergic rhinitis was reported in 58.0% cases. Eczema was associated with 16.0% patients; however, only 4% patients had associate conjunctivitis. Conclusion: In conclusion young male is more commonly affected by cough variant asthma of which majority have family history of asthma. Journal of National Institute of Neurosciences Bangladesh, 2016;2(1):30-33